(untitled) (World Bulletin of Public Health, 2025)
Today, the necessity of using complete removable prosthetics comprises 15-46% among patients aged 45 to 75 years. However, according to WHO data, 26% of patients do not use plate prostheses for various reasons, one of which is the unsatisfactory quality of artificial dentition. It should also be noted that the average service life of a plate prosthesis is about 5 years. Therefore, the task of increasing the functional value of removable prostheses remains relevant